Local and controlled release of tamoxifen from multi (layer-by-layer) alginate/chitosan complex systems. (15th February 2019) - Criado-Gonzalez, Miryam; Fernandez-Gutierrez, Mar; San Roman, Julio; Mijangos, Carmen; Hernández, Rebeca
Highlights: Polysaccharide films for local TMX release were prepared by spray layer-by-layer. TMX release was modulated by the number of bilayers of the polysaccharide films. TMX was released for up to 10 days and breast cancer cell viability decreased to 36%. Abstract: Herein, multilayer polysaccharide films were proposed and characterized as biomaterials for the local and controlled release of an antitumoral drug. To that aim, multilayer films of alginate (Alg) and chitosan (Chi) were built up through spray assisted layer-by-layer (LbL) technique employing an automatic equipment. A specific drug against breast cancer, tamoxifen (TMX), was incorporated in different intermediate positions of the multilayer Alg/Chi films. Our findings highlight that Alg/Chi multilayer films can be employed for sustained and local TMX delivery and their therapeutic effect can be modulated and optimized by the number of bilayers deposited over the loaded tamoxifen, the quantity of tamoxifen loaded in several intermediate positions and the total area of the film.